2019
DOI: 10.3168/jds.2019-16759
|View full text |Cite
|
Sign up to set email alerts
|

The effect of length of storage and sodium benzoate on the nutritive value of reconstituted sorghum grain silages for dairy cows

Abstract: Twenty Holstein cows at 168 ± 87 d in milk (mean ± SD) were assigned to a 4 × 4 Latin square design with a 2 × 2 factorial arrangement to evaluate the effects of 2 storage lengths (30 or 90 d) and the presence of sodium benzoate (control or 0.2% as fed) on the nutritive value of reconstituted sorghum grain silages (RSGS). For each treatment, dry ground sorghum grain was rehydrated to 35% moisture and ensiled in 200-L plastic drums. The treatments were RSGS stored for 30 d without sodium benzoate ( 30CON), RSGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The lower DM content at 90 days of fermentation compared to 60 days, except for the 0.3% dose of the enzyme (see Supplementary Fig. S6 ), was probably due to microbial activity during the fermentation process, which naturally promotes reductions in DM contents with advancing ensiling time, as verified by Carvalho et al 11 and Da Silva et al 3 on CG silages and Santos et al 13 on rehydrated SG silage.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The lower DM content at 90 days of fermentation compared to 60 days, except for the 0.3% dose of the enzyme (see Supplementary Fig. S6 ), was probably due to microbial activity during the fermentation process, which naturally promotes reductions in DM contents with advancing ensiling time, as verified by Carvalho et al 11 and Da Silva et al 3 on CG silages and Santos et al 13 on rehydrated SG silage.…”
Section: Discussionmentioning
confidence: 68%
“…Increased in situ starch digestibility of rehydrated corn grain silage was observed by Fernandes et al 12 after 120 days of fermentation, compared to corn at ensiling, with values of 92.0 and 72.0%, respectively. For rehydrated sorghum grains silage, Santos et al 13 observed that cows fed diets containing silages stored for 30 days had lower starch digestibility (86.9%) compared to cows fed diets with silages stored for 90 days (89.3%).…”
Section: Introductionmentioning
confidence: 99%